Cognitive functioning transitions, health expectancies, and inequalities among elderly people in China: A nationwide longitudinal study. (11th September 2018) - Hou, Chengbei; Lin, Yinan; Ren, Ming; Liu, Mengyang; Ma, Yuan; Li, Haibin; Tao, Lixin; Wang, Wei; Li, Xia; Fang, Xianghua; Guo, Xiuhua
Abstract : Objective: In China, cognitive impairment has become a huge challenge owing to the rapid aging process. We investigate cognitive health expectancy and potential factors leading to inequalities of cognitive health for Chinese older people. Methods: The study included 19 943 participants aged 65 to 95 at the first observation in Chinese Longitudinal Healthy Longevity Survey collected during 2002‐2014. Cognitive impairment was categorized into none, mild, and severe by the score of cMMSE. Multistate models based on continuous‐time Markov process were applied to calculate cognitive health expectancies and estimate hazard ratio from no impairment to impairment for potential factors. Results: Urban women and men aged 65 were expected to spend 31.18% and 19.82% of their remaining 17.46 and 15.45 years with cognitive impairment; meanwhile, rural women and men aged 65 were expected to spend 35.31% and 21.39% of their remaining 16.73 and 14.87 years with cognitive impairment. Women achieving lower educational attainment (HR1‐6 years  = 0.78, 95% CI, 0.71‐0.87; HR7+ years  = 0.59, 95% CI, 0.49‐0.70) than men and rural residents having less access to medical service (HR = 0.79, 95% CI, 0.68‐0.92) and doing less regular exercise (HR = 0.87, 95% CI, 0.80‐0.96) than urban people caused the differences of cognitive health for genders and regions. Conclusions: Women and rural people experience less cognitive health expectancies compared with their counterparts, respectively. Chinese government should pay more attention to rural women and make efforts to reduce the inequalities of cognitive health by increasing opportunities of education for women and improving access to medical service and healthy lifestyle for rural people.